THE ROLE OF INTERNAL AUDIT IN GOVERNANCE, RISK MANAGEMENT, AND CONTROLS FOR FRAUD PREVENTION AT PPATK - Bambang Hadi Purnomo (Association of Certified Fraud Examiners Indonesia Chapter, 2017)
ABSTRACTLaw Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering has mandated the Indonesian Financial Transaction Reports and Analysis Centre (INTRAC / PPATK) to be the focal point of every effort made to combat money laundering in Indonesia. As a focal point, PPATK receives financial transaction reports from reporting parties, which include Financial Service Providers and Goods and Services Providers, where the data provided are considered to be highly confidential. This indicates that PPATK has become a strategic institution, and thereby it should be assured that its governance, risk management, and internal control are well maintained. Government Internal Supervision Apparatus (APIP) has become more strategic and keeps its pace according to the latest needs. APIP is expected to be the agent of change that could create added-values into the products or services made by the government agency. The activity of internal audit from APIP should contribute to increase the effectiveness and efficiency of governance, risk management, and control processes. In term of risk management, internal auditor should be able to evaluate the effectiveness and his contribution towards the improvement of the risk management process. Internal auditor should monitor the process through sustainable management, separated evaluation, or both. Internal auditor should be able to evaluate the potential occurrence of fraud and how the auditee manages the fraud risk. Meanwhile, in relation to internal control, the activity of internal auditor should evaluate the adequacy and effectiveness of internal control in handling the risks of the auditee’s governance, operational, and information system.